Belinostat suppresses cell proliferation by inactivating Wnt/β-catenin pathway and promotes apoptosis through regulating PKC pathway in breast cancer. Issue 1 (4th December 2019) - Lu, Pengwei; Gu, Yuanting; Li, Lin; Wang, Fang; Yang, Xue; Yang, Yunqing
Abstract: Belinostat is a histone deacetylase inhibitor drug capable of regulating cell growth in diverse cancers. Nonetheless, little information clarified the role of Belinostat in breast cancer. Hence, the functions of Belinostat in breast cancer cells survival was disclosed in this study. Belinostat at 50 and 100 μM were applied to manage MCF-7 cells, cell viability, Ki67 positive cells, cell cycle and apoptosis were monitored via MTT, immunohistochemistry and flow cytometry. Furthermore, the apoptosis-related factors, Wnt/β-catenin pathway and PKC pathway were tested through western blot and qRT-PCR. Lastly, in vivo effect of Belinostat was determined by a murine model. The results showed that Belinostat dampened cell viability, decreased the proportion of Ki67 positive cells and arrested cells at G0/G1 phase. The decreases of Wnt/β-catenin, CCND2 and Myc were observed in MCF-7 cells after Belinostat stimulation. Additionally, Belinostat induced cell apoptosis, meanwhile dampened Bcl-2 and raised Bax and Cleaved caspase 3 in a dose and time-dependent manner. Additionally, Belinostat activated PKC pathway by upgrading PKCδ and P53 expressions. Furthermore, Belinostat restrained tumour weight and volume in vivo . In summary, this study depicted that Belinostat prohibited proliferation and evoked apoptosis via mediating Wnt/β-catenin and PKC pathways in MCF-7 cells.